The Efficiency Implications of Earnings Retentions: An Extension - Shapiro, Daniel M.; Sims, William A.; Hughes, Gwenn (The Review of Economics and Statistics, 1983)
This paper reports on another attempt to statistically uncover evidence of embodied technological change as an explanation of changes in labor productivity in the United States. In this version of the test, an interregional cross-section, time-series sample of data was used. While the hypothesis has a lot of appeal, it has proven difficult to find manifestations of embodiment in econometric tests. This study has proven to be no exception. Despite the unique data set, results were again not supportive of the hypothesis. A possible limitation of this test is that the time period studied may have been too short. REFERENCES